Three-dimensional models for studying neurodegenerative and neurodevelopmental diseases - Tsaridou, Stavroula; Skamnelou, Margarita; Iliadou, Marianna; Lokka, Georgia; Parlapani, Evangelia; Mougkogianni, Maria; Danalatos, Rodolfos-Iosif; Kanellou, Anastasia; Chlorogiannis, Dimitris-David; Kyrousi, Christina; Taraviras, Stavros (GeNeDis 2018: Genetics and Neurodegeneration, 2020)
Human brain possesses a unique anatomy and physiology. For centuries, methodological barriers and ethical challenges in accessing human brain tissues have restricted researchers into using 2-D cell culture systems and model organisms as a tool for investigating the mechanisms underlying neurological disorders in humans. However, our understanding regarding the human brain development and diseases has been recently extended due to the generation of 3D brain organoids, grown from human stem cells or induced pluripotent stem cells (iPSCs). This system evolved into an attractive model of brain diseases as it recapitulates to a great extend the cellular organization and the microenvironment of a human brain. This chapter focuses on the application of brain organoids in modelling several neurodevelopmental and neurodegenerative diseases.